2018
DOI: 10.1002/ppap.201800052
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of cold atmospheric plasma anti‐cancer efficacy in triple‐negative breast cancers

Abstract: Cold atmospheric plasma has emerged as a novel oncotherapeutic approach that has undergone a fast growth in the past few years. However, there is no quantitative assessment of the factors influencing its anti-tumor efficacy and the mechanism driving its activity remains mysterious. Through the use of 18 orthogonal experiments followed by linear model construction, we identified four deterministic parameters, that is, "treatment time," "liquid surface area," "thickness of medium," and "number of cells," which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…Thus, direct comparison of the cell viability cannot be made between 3 lpm and 1 lpm despite the same power setting and treatment time due to different beam length, well size, medium volume, and cell number between the two conditions. This was also reported repeatedly by other researchers worldwide [33,34]. This study intends to focus on the introduction of the Canady Cold Plasma Conversion System and its efficacy on the treatment of triple-negative breast cancer for both flowrates.…”
Section: Discussionsupporting
confidence: 53%
“…Thus, direct comparison of the cell viability cannot be made between 3 lpm and 1 lpm despite the same power setting and treatment time due to different beam length, well size, medium volume, and cell number between the two conditions. This was also reported repeatedly by other researchers worldwide [33,34]. This study intends to focus on the introduction of the Canady Cold Plasma Conversion System and its efficacy on the treatment of triple-negative breast cancer for both flowrates.…”
Section: Discussionsupporting
confidence: 53%
“…This is because the treatment conditions, including well size, beam length, media volume, and cell number, are different between these two assays, and Yan et al demonstrated that those conditions can alter the effect of CAP on cell viability [17,20]. Xu et al have suggested a formula to compare plasma dose among treatment conditions within one cell type and this may be necessary to compare future results [40].…”
Section: Discussionmentioning
confidence: 99%
“…PAM was found to convey selectivity in multiple types of cancer cells including, e.g., melanoma [12], breast cancer [13,14] and head and neck carcinomas [15]. However, relatively little was reported on the e cacy of PAM in killing prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…CAP has been widely applied in many bio-related elds such as bacterial disinfection, cell transfection, dentistry and wound healing [7][8][9][10][11], with its selectivity against cancer cells being rstly reported in 2007 [12]. Ever since, CAP was shown effective in treating multiple types of tumors such as breast cancer [13,14]. Clinically, CAP was shown to be effective in partially alleviating super cial head and neck tumors and effectively reducing ulceration caused by cancers [15].…”
Section: Introductionmentioning
confidence: 99%